Are impatient farmers more risk-averse? Evidence from a lab-in-the-field experiment in rural Uganda. Issue 2 (8th January 2017) - Clot, Sophie; Stanton, Charlotte Y.; Willinger, Marc
ABSTRACT: Based on data from a field-experiment in rural Uganda, we show that impatient farmers are more risk-averse than patient farmers. We relied on a simplified version of the Convex Time Budget (CTB) method to elicit farmers' time preferences and on an independent method for eliciting their risk-preferences. We report two important findings. First, we show that our simplified CTB method applied to farmers from Uganda replicates the key findings of Andreoni and Sprenger's lab experiments that involved student subjects. Second, we establish the existence of a negative correlation between risk tolerance and impatience, based on two independent measures.